Reversibility of Cardiac Function Predicts Outcome After Transcatheter Aortic Valve Replacement in Patients With Severe Aortic Stenosis. Issue 7 (11th July 2017) - Sato, Kimi; Kumar, Arnav; Jones, Brandon M.; Mick, Stephanie L.; Krishnaswamy, Amar; Grimm, Richard A.; Desai, Milind Y.; Griffin, Brian P.; Rodriguez, L. Leonardo; Kapadia, Samir R.; Obuchowski, Nancy A.; Popović, Zoran B.
Abstract : Background: Reversibility of left ventricular (LV) dysfunction in high‐risk aortic stenosis patient and its impact on survival after transcatheter aortic valve replacement (TAVR) are unclear. We aimed to evaluate longitudinal changes of LV structure and function after TAVR and their impact on survival. Methods and Results: We studied 209 patients with aortic stenosis who underwent TAVR from May 2006 to December 2012. Echocardiograms were used to calculate LV end‐diastolic volume index (LVEDVi), LV ejection fraction, LV mass index (LVMi), and global longitudinal strain before, immediately (<10 days), late (1–3 months), and yearly after TAVR. During a median follow‐up of 1345 days, 118 patients died, with 26 dying within 1 year. Global longitudinal strain, LVEDVi, LV ejection fraction, and LVMi improved during follow‐up. In patients who died during the first year, death was preceded by LVEDVi and LVMi increase. Multivariable longitudinal data analysis showed that aortic regurgitation at baseline, aortic regurgitation at 30 days, and initial LVEDVi were independent predictors of subsequent LVEDVi. In a joint analysis of longitudinal and survival data, baseline Society of Thoracic Surgeons score was predictive of survival, with no additive effect of longitudinal changes in LVEDVi, LVMi, global longitudinal strain, or LV ejection fraction. Presence of aortic regurgitation at 1 month after TAVR was the only predictor of 1‐year survival. Conclusions: LV reverse remodeling was observed after TAVR, whereas lack of LVEDVi and LVMi improvement was observed in patients who died during the first year after TAVR. Post‐TAVR, aortic regurgitation blocks reverse remodeling and is associated with poor 1‐year survival after TAVR.